Erythropoietic Polyploidy IV. Erythropoietic Polyploidy due to I131 Treatment of Thyroid Disorders - Jan, Nemec, M.D.; Hugo, Polák, M.D. (Nuklearmedizin - NuclearMedicine, 1964)
The degree of erythropoietic polyploidy (expressed by the index: IEP) of the bone marrow in 8 patients with thyroid cancer and 5 cases with thyrotoxicosis, both treated with radioiodine, has been studied. It was found that:1. the incidence of polyploid erythroblasts after administration of diagnostic doses of I131, compared with a group of healthy persons is slightly but significantly enhanced,2. after the administration of therapeutic doses in patients suffering from thyrotoxicosis or thyroid cancer, a further rise of erythropoietic polyploidy occurred in the early phase of therapy (up to 2 months), as compared with the values found after diagnostic doses only,3. in a later phase after radioiodine administration (3 months — 6 years), an increase of the number of polyploid erythroblasts was established only in those bone marrows which showed erythroid hyperplasia. In marrows with a hypoplastic erythroid series the IEP value was normal.Since the determination of the IEP is neither difficult nor time-consuming, the possibility of the use of this index for the assessment of changes caused by minute radiation doses is considered.Le degré d’une polyploïdie érythropoiétique de la moelle osseuse (exprimé par l’indice IEP) a été étudié après traitement avec radioiode chez 8 malades avec un cancer du corps thyroïdien et 7 malades avec thyréotoxicose. On a observé 1. une augmentation faible mais significative de la fréquence d’érythroblastes polyploïdes après l’application de doses diagnostiques de I131 par rapport à un groupe de personnes saines, 2. une augmentation continue de polyploïdie érythropoïetique dans les premiers deux mois après la thérapie avec des doses thérapeutiques chez des malades souffrant d’une thyréotoxicose ou d’un cancer du corps thyroïdien 3. une augmentation du nombre des èrythroblastes polyploïdes dans une phase postérieure après l’application de radioiode (3 mois — 6 ans) seul chez les malades qui souffraient d’une hyperplasie érthyropoïétique de la moelle osseuse. Chez des malades où l’érythropoïèse était hypoplastique, l’IEP était normal.Etant donné que la détermination de l’IEP n’est pas difficile et n’exige pas de temps, la possibilité de son application pour constater des changements par suite des plus petites doses de rayons est discutée.Es wurde das Ausmaß einer erythropoetischen Polyploidie des Knochenmarks (ausgedrückt durch den Index: IEP) bei 8 Patienten mit Schilddrüsenkrebs und 5 Patienten mit Thyreotoxikose nach Behandlung mit Radiojod untersucht. Es wurde beobachtet, daß 1. die Häufigkeit von polyploiden Erythroblasten nach Verabreichung diagnostischer Dosen von J131 im Vergleich zu einer Gruppe von gesunden Personen leicht, aber signifikant erhöht ist, 2. nach Verabreichung von therapeutischen Dosen an Personen mit Thyreotoxikose oder Schilddrüsenkrebs eine weitere Erhöhung der erythropoetischen Polyploidie in den ersten 2 Monaten nach Therapie auftritt, 3. daß in einer späteren Phase nach Radiojodverabreichung (3 Monate bis 6 Jahre) die Erhöhung der Anzahl der polyploiden Erythroblasten nur bei jenen Patienten beobachtet werden konnte, bei denen eine erythropoetische Hyperplasie des Knochenmarks vorlag. Bei Patienten, bei denen die Erythropoese hypoplastisch war, war der IEP normal.Da die Bestimmung des IEP weder schwierig noch zeitraubend ist, wird die Möglichkeit seiner Verwendung für die Feststellung von Veränderungen im Gefolge kleinster Strahlendosen diskutiert.